STRATEGI PENGEMBANGAN (LEMBAGA PENYIARAN PUBLIK) LPP TVRI MELALUI REBRANDING LOGO BARU: PERSPEKTIF INDUSTRI MEDIA ISLAM - Ulfi Nurfaiza (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
TVRI (Televisi Republik Indonesia) seeks to provide wise information for the public. However, because in the current era of the rapid rise of the media industry, it is very important that the TVRI Public Broadcasting Institution re-emerges before the public with a new identity as a counterweight and news highlight that is able to voice community rights and promote cultural values and local wisdom. In rebranding, there are a number of things carried out by LPP TVRI namely implementing the Power Marketing mindset, which lies in 3 keys, first moving is done before TVRI rebranding can be passed from Kepsta, starting to form a small team for rebranding preparation. Second, Caring (caring) by involving every community and having innovation in developing companies such as the emergence of a new program ‘’ Good Morning East Java ‘’ which has the aim to greet residents and serve the East Java people. Third, Innovation is an effort of LPP TVRI to produce new products and innovations to move forward with the aim of being an institution that has a vision and mission for unifying the nation. This can be seen in the change in the new logo, color and organizational culture.In the perspective of the Islamic Media Industry, Islam is a religion that strongly advocates for creating brotherhood and unity of various differences. TVRI as public television also implements as its slogan the unifying media of the nation, naturally responsible as a media that is able to disseminate interesting information with the aim of being a media that is able to serve the public so as to create brotherhood.